Cold Regions Engineering 2015 : developing and maintaining resilient infrastructure : proceedings of the 16th International Conference on Cold Regions Engineering : July 19-22, 2015, Salt Lake City, Utah - Guthrie, W. Spencer (American Society of Civil Engineers, 2015)
This collection contains 55 peer-reviewed papers addressing the challenges of developing and maintaining resilient infrastructure in cold climates. In addition to issues and solutions related to the built environment, the papers also provide a deeper understanding of the processes of freezing and thawing as they occur in the surrounding natural environment. Topics include: buildings and bridges; hydraulics and hydrology; pavement materials, structures, and maintenance; frozen soil properties, ground characterization, and frost heave; embankments and foundations; utilities and energy; and construction and logistics. --